2020
DOI: 10.1371/journal.pone.0239705
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of Respiratory Burst Oxidase Homolog genes in six Rosaceae species and an analysis of their effects on adventitious rooting in apple

Abstract: Adventitious root formation is essential for plant propagation, development, and response to various stresses. Reactive oxygen species (ROS) are essential for adventitious root formation. However, information on Respiratory Burst Oxidase Homolog (RBOH), a key enzyme that catalyzes the production ROS, remains limited in woody plants. Here, a total of 44 RBOH genes were identified from six Rosaceae species (Malus domestica, Prunus avium, Prunus dulcis 'Texas', Rubus occidentalis, Fragaria vesca and Rosa chinensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 60 publications
(97 reference statements)
5
28
0
Order By: Relevance
“…Prediction programs for subcellular localization showed that the seven CsRboh proteins were localized in the cell membrane. The results are in agreement with those obtained in other studies [ 10 , 13 , 14 , 16 , 28 ], suggesting Rbohs’ potential role in the regulation of ROS generation. Notably, few Rboh proteins were predicted to localize in chloroplast thylakoid membranes or mitochondria.…”
Section: Discussionsupporting
confidence: 93%
“…Prediction programs for subcellular localization showed that the seven CsRboh proteins were localized in the cell membrane. The results are in agreement with those obtained in other studies [ 10 , 13 , 14 , 16 , 28 ], suggesting Rbohs’ potential role in the regulation of ROS generation. Notably, few Rboh proteins were predicted to localize in chloroplast thylakoid membranes or mitochondria.…”
Section: Discussionsupporting
confidence: 93%
“…To further define the relationship between MdWRKY87 expression levels and adventitious rooting formation, we next examined the expression pattern of MdWRKY87 during adventitious rooting formation of tissue culture plantlets in apple. According to the paraffin sections of stem bases of apple plantlets, we found that primordia with dome-shaped adventitious structures were clearly visible at 6~9 days after transplanting ( Figure 1E ) as our previous results ( Cheng et al., 2020 ). After 12 days of transplantation, adventitious roots began to appear.…”
Section: Resultssupporting
confidence: 88%
“…The expression of MdWRKY87 is positively correlated with auxin-induced adventitious root formation. dome-shaped adventitious structures were clearly visible at 6~9 days after transplanting (Figure 1E) as previous results (Cheng et al, 2020).…”
Section: Mdwrky87 Expression Correlates Positively With Adventitious ...supporting
confidence: 89%
See 2 more Smart Citations